2012
DOI: 10.2522/ptj.20110124
|View full text |Cite
|
Sign up to set email alerts
|

Early Neuromuscular Electrical Stimulation to Improve Quadriceps Muscle Strength After Total Knee Arthroplasty: A Randomized Controlled Trial

Abstract: The early addition of NMES effectively attenuated loss of quadriceps muscle strength and improved functional performance following TKA. The effects were most pronounced and clinically meaningful within the first month after surgery, but persisted through 1 year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
351
2
35

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 218 publications
(398 citation statements)
references
References 64 publications
10
351
2
35
Order By: Relevance
“…Previous work performed by the authors [51,53] suggested that 25 patients (50 knees) would be required to achieve 90% power to detect a small to moderate effect of tourniquet use on quadriceps strength at 3 weeks postoperatively, the primary variable of this report. Because leg dominance was not formally assessed in this study, it is conceivable that-by chance-the tourniquet could have been applied to the nondominant leg a greater proportion of the time, thus confounding outcomes in favor of the notourniquet group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work performed by the authors [51,53] suggested that 25 patients (50 knees) would be required to achieve 90% power to detect a small to moderate effect of tourniquet use on quadriceps strength at 3 weeks postoperatively, the primary variable of this report. Because leg dominance was not formally assessed in this study, it is conceivable that-by chance-the tourniquet could have been applied to the nondominant leg a greater proportion of the time, thus confounding outcomes in favor of the notourniquet group.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative deficits in quadriceps strength may be particularly problematic because there is reason to believe that early strength loss, occurring primarily through deficits in voluntary muscle activation [36], may actually exacerbate long-term weakness [24]. In fact, there is a growing body of research focused on improving TKA rehabilitation specifically to limit early postoperative loss of quadriceps strength [31,53]. Moreover, for patients undergoing TKA, quadriceps strength is one of the most robust predictors of long-term function in tasks such as chair-rise and stairclimbing ability [35,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were given visual targets from the dynamometer's output and strong verbal encouragement during each trial. Maximal voluntary isometric contractions for all muscle groups were performed twice; however, if maximal torque during the first two trials differed by more than 5%, a third trial was performed, as previously described [18,[46][47][48]. The trial with the highest torque was normalized to body mass (kg) and used for analysis [1].…”
Section: Strength Testing Proceduresmentioning
confidence: 99%
“…Se emplea con la idea de ejercitar la contracción muscular y mejorar su resistencia. Algunos autores recomiendan su uso en el músculo cuádriceps, después de la ATR, a pesar de su limitada evidencia (108). Una revisión Cochrane del año 2010 no recomienda su utilización debido al bajo grado de evidencia disponible (109).…”
Section: Movilización Precoz Rehabilitación Postquirúrgicaunclassified